Trends of spiritual processes in new Uzbekistan (Diversity Research: Journal of Analysis and Trends, 2024)
In this article, the trends of spiritual processes in the new Uzbekistan and the issues of bringing this system to a higher level are studied, highlighting that the issue of attitude to democracy is extremely important in our national spirituality in the formation of an active citizenship position in the new Uzbekistan.